Islamic Movements and Their Role In Politics In Turkey - Nezir Akyeşilmen; Arif Behiç Özcan (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Various opinions, institutions and individuals have influenced the political life in Turkey which constructed on a parliamentary democracy. Developments and refracting in the process of democratization and modernization have changed the roles, quality and quantity of the elements in Turkey’s political life. The affects of these elements increased and decreased in time. In this context, the role of Islamic movements in politics cannot be denied in Turkey, particularly in the recent years. Starting with the development of multi-party democracy, after the 1950’s a number of developments greatly advanced Turkey's democratization and modernization. These same events also transformed politics in Turkey which provided the environment for the growth of Islamic parties in Turkey. First, this paper, regarding these developments, discusses how to make a clarification of Islamic movements in Turkey as they are the parts of Turkey’s political life. Secondly, we try to demonstrate how different Islamic movements determine the political behaviors in their groups if they really do that. After discusses Islamic movements during oneparty rule up until 1950, the paper focuses on the transition to multi-party democracy and then the resurgence of those movements. In the last part, just before the conclusion, electoral behavior of Islamic movements will be analyzed one by one. In this paper, we examine some main stream Islamic movements’ structures and effects in Turkey’s political life like Nurist Movements Nurcu Hareket , Gulen Movement Gulen Hareketi , New Asia Yeni Asya , Suleymanists Suleymancilar , National Sight Milli Gorus , Nakshibendi Order Naksibendiler , Iskenderpasha Order Iskenderpasa Cemaati and Menzil Movement Menzilciler . We will consider the table which developed by authors based on data gathered from different sources. The analysis depended on this table shows political behaviors of these Islamic movements in the general elections between 1950-2011. Of course, a different analysis could develop our results or reach different results anytime